The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/md.0000000000012454
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane addiction due to workplace exposure

Abstract: Rationale:Anesthesiologists have a well-known increased risk of substance abuse. High-concentration of inhalation anesthetics in exhaled air of operating room personnel is detected. such secondhand exposure produces neurobiological sensitization to the reinforcing effects of inhalation anesthetics.Patient concerns:An addictive young male anesthesiologist who was long-term abuse with sevoflurane after 4 years occupational exposure. A 28-year-old anesthesiologist on duty was found deeply sleep in the locker room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Inhalational anesthetics have been reported to account for 2% of drug abuse among anesthesiologists in the United States and 5% in Australia and New Zealand [ 7 , 29 ]. Though inhalational anesthetics were not generally regarded as addictive drugs in the past, recently, more and more reports have shown that they also have abuse potential [ 30 , 31 ]. In a survey of inhalational anesthetic abuse in anesthesia training programs, nitrous oxide (N 2 O), isoflurane, sevoflurane, halothane, and desflurane accounts for 47%, 24%, 19%, 19%, and 9.5%, respectively.…”
Section: The Current Situation Of Non-opioid Anesthetics Addictionmentioning
confidence: 99%
“…Inhalational anesthetics have been reported to account for 2% of drug abuse among anesthesiologists in the United States and 5% in Australia and New Zealand [ 7 , 29 ]. Though inhalational anesthetics were not generally regarded as addictive drugs in the past, recently, more and more reports have shown that they also have abuse potential [ 30 , 31 ]. In a survey of inhalational anesthetic abuse in anesthesia training programs, nitrous oxide (N 2 O), isoflurane, sevoflurane, halothane, and desflurane accounts for 47%, 24%, 19%, 19%, and 9.5%, respectively.…”
Section: The Current Situation Of Non-opioid Anesthetics Addictionmentioning
confidence: 99%